Respuesta :

Plug in y into the other y

X-2 = -x + 4

Put unknowns on one side and knowns on other side

2x = 6

X= 3

No need to find y because only 1 answer has 3 as x.

Answer is (3,1)

Answer:

Option c

(3,1)

Step-by-step explanation:

Solving system of equations:

y = -x + 4  ----------(I)

y = x - 2 -----------(II)

Add equation (I) & (II). So, x will be eliminated and we can find the value of y.

      (I)       y = -x + 4

     (II)       y = x -  2   {Now add}

               2y = 2

Divide both sides by 2

                y = 2/2

y =1

Substitute y = 1 in any of the equations. Here, we are substituting in equation  (II)

1 = x - 2

1 + 2 = x

x = 3